Harmonizing Adat Obligations and State Law: A Case Study of Murder and Rape Cases in Baduy’s Indonesia - Yulia, Rena; Prakarsa, Aliyth; Bustami, Mohammad Reevany (Journal of Indonesian Legal Studies, 2023)
This study endeavors to examine the execution of adat obligation fulfillment within the Baduy adat society, specifically in cases involving the murder and rape of Baduy girls in 2019. The primary focus is on scrutinizing how the Baduy adat institution has undertaken the fulfillment of adat obligations in these cases and its alignment with the provisions outlined in the New Criminal Code. Employing a normative-sociological research methodology, both secondary and primary data were utilized, including a comprehensive literature review and field studies conducted through interviews with traditional leaders in Baduy. The imperative nature of this research lies in its investigation into the applicability of positive law within the Baduy adat area, coupled with the implementation of adat obligations and the restoration of cosmic balance within Baduy society following the repercussions of crimes within the Baduy adat jurisdiction. The distinctive contribution of this research lies in its exploration of the fulfillment of adat obligations applicable in Baduy, particularly in cases involving the murder and rape of Baduy girls, and its correlation with the regulations of the New Criminal Code. The research findings underscore that perpetrators of the mentioned crimes are subject to penalties under both positive criminal law (imprisonment) and Baduy's adat law, where an adat obligation mandates them to marry the victim. Notably, the implementation of sanctions from both state and adat law occurs concurrently, despite originating from distinct institutional frameworks. In conclusion, the fulfillment of adat obligations, as orchestrated by Baduy's adat law, aligns with the regulations in the New Criminal Code. However, the execution of adat obligations in accordance with the New Criminal Code necessitates a court decision. Consequently, the role of the adat institution assumes critical importance concerning its relevance and authority in sanctioning within the implementation of adat obligations.